The impact of primary care access on autism spectrum disorder awareness in an underserved population - O’Donnell, Mackenzie T.; Schmidt, Randall B.; Butler, Faith M. (Frontiers in Public Health, 2023)
American Academy of Pediatrics (AAP) recommendations for Autism Spectrum Disorder (ASD) screening do not specifically address safety-net clinics, which provide multidisciplinary healthcare services to underserved patients. This project explored the potential for ASD screening in safety-net clinics by assessing parental perceived knowledge of ASD at JayDoc Free Clinic, a student-run safety-net clinic in Wyandotte County, Kansas. May through December 2022, patients who reported to be the parent of a minor received a demographic survey and a Likert-style questionnaire assessing perceived knowledge of ASD, including understanding the importance of ASD screening and ASD signs and symptoms. Responses were categorized into positive, negative, and unsure. Demographic variables included the minor's primary care provider (PCP) status. Results were analyzed using bivariate analysis, with chi-square tests for significance (p-value ≤ 0.05). Of the 52 participants who completed at least one Likert response, 55.8% reported their child had a PCP. Responses were somewhat balanced with 44.2% positive for understanding the importance of ASD screening and 53.8% positive for understanding ASD signs and symptoms. For understanding the signs and symptoms of ASD, an unsure response (32.7% of responses) was statistically associated with a lack of PCP (p=0.017). The balance of positive with negative and unsure responses could reflect lack of ASD knowledge and may relate to healthcare inaccessibility. This is consistent with the significant association between lack of PCP and unsure responses for understanding ASD signs and symptoms. ASD screening and education in safety-net clinics like JayDoc could be valuable, particularly for children without a PCP.